Rural community culture: a critical analysis of two communities' perceptions of agricultural focused community development through a directed facilitation approach - Plaschka, Russell E. (Kansas State University, 2022)
Rural development has historically been focused on the American farmer. With changes in demographics and shifting populations, the plight of the rural community has more recently been the focus of governmental programming. The focus of this study centers on the topic of rural community development as viewed through the lens of social constructionism using critical discourse analysis to answer the question: How do Strategic Growth Initiative directed facilitations intersect with community members’ ideas, traditions, visions, and values among community members in achieving community-driven community development, from participant perspectives? The purpose was to develop a deeper understanding of the perceptions rural communities have toward agriculture, the government’s role in community development, and facilitation as a means to generate consensus on possible paths forward. Two rural communities were selected to participate in facilitated discussions centered on agriculture as a vehicle for community development. From the participants of the facilitated meetings, four individuals, two from each county, were selected to participate in interviews. The individuals represented geographic and demographic diversity in line with their respective counties. The analysis of the responses revealed that all participants agree that agriculture is the main economic driver and should be the foundation from which to build community and economic development. Further analysis revealed that the community members welcome community development resources from governmental agencies but felt more input from the local level is needed when determining the best use within their communities/regions. Additionally, the data illustrated participants valued the facilitated approach to gathering community members, soliciting ideas, and having difficult conversations around specific agricultural activities that would or could benefit their regions. The findings of this study shed light on the perceptions of rural communities and their desire to grow or at least sustain their communities. The recommendations to community developers are to be purposeful in ensuring all community voices are valued and understood. Further, policy makers, those who develop community development programs, should be mindful that rural communities are not all structured and populated the same and that flexibility must be built into programs so that local community members can best utilize the resources.
Keywords: Rural; Agriculture; Community development; Directed facilitation